Identifying trustworthy experts: how do policymakers find and assess public health researchers worth consulting or collaborating with? - Abby S Haynes; Gemma E Derrick; Sally Redman; Wayne D Hall; James A Gillespie; Simon Chapman; Heidi Sturk (PLoS ONE, 2012)
This paper reports data from semi-structured interviews on how 26 Australian civil servants, ministers and ministerial advisors find and evaluate researchers with whom they wish to consult or collaborate. Policymakers valued researchers who had credibility across the three attributes seen as contributing to trustworthiness: competence (an exemplary academic reputation complemented by pragmatism, understanding of government processes, and effective collaboration and communication skills); integrity (independence, "authenticity", and faithful reporting of research); and benevolence (commitment to the policy reform agenda). The emphases given to these assessment criteria appeared to be shaped in part by policymakers' roles and the type and phase of policy development in which they were engaged. Policymakers are encouraged to reassess their methods for engaging researchers and to maximise information flow and support in these relationships. Researchers who wish to influence policy are advised to develop relationships across the policy community, but also to engage in other complementary strategies for promoting research-informed policy, including the strategic use of mass media.